Risks and ways of preventing kidney dysfunction in drug-induced immunosuppression in solid organ recipients - Sh. R. Galeev; S. V. Gautier (Вестник трансплантологии и искусственных органов)
Immunosuppressive therapy (IMT) is the cornerstone of treatment after transplantation. The goal of immunosuppression is to prevent acute and chronic rejection while maximizing patient survival and long-term graft function. However, the expected effects of IMT must be balanced against the major adverse effects of these drugs and their toxicity. The purpose of this review is to summarize world experience on current immunosuppressive strategies and to assess their effects on renal function.